The Multivariate Split Normal Distribution and Asymmetric Principal Components Analysis - Mattias Villani; Rolf Larsson (Sveriges Riksbank, 2004)
The multivariate split nomal distribution extends the usual multivariate normal distribution by a set of parameters which allows for skewness in the form of contraction/dilation along a subset of the prinicpal axis. The paper derives some properties for this distribution, including its moment generating function, multivariate skewness and kurtosis. Maximum likelihood estimation is discussed and a complete Bayesian analysis of the multivariate split normal distribution is developed.
Keywords: C11; C16; 330; Bayesian inference; Elicitation; Estimation; Maximum likelihood; Multivariate analysis; Skewness